Education and training to support radiation protection research in Europe: the DoReMi experience. (18th January 2019) - Ottolenghi, Andrea; Trott, Klaus-Rüdiger; Smyth, Vere
Abstract: A review is presented to the program of education and training setup within the DoReMi Network of Excellence. DoReMi was funded by Euratom under the EU 7th Framework Programme to coordinate the EU research into risks from low-dose ionizing radiation. It was seen to be necessary to form a network of expert institutions in order to tackle the scientific questions with the resources available. From the start, importance was given to the need to stimulate and support education and training to build up the capability of the research community. DoReMi dedicated a workpackage to education and training that put in place a number of activities that have been successful in attracting new students into the area and introducing research scientists to new topic areas and technologies. The program of education and training in DoReMi provided a significant contribution to the low-dose radiation research community and has been further developed and extended in the following Euratom-funded project OPERRA and the European Joint Programme CONCERT.